(untitled) (Research, Society and Development, 2023)
Introduction: In consideration of the need for constant communication and exchange of experiences to obtain knowledge, academic monitoring plays out a fundamental tool in the teaching-learning process. This study aims to evaluate the impact of the Peer-Assisted Learning (PAL) program on the development of its participants, with the goal of improving professional skills for the professional market. Objectives: This study analyzes the perception of those involved in the PAL program and the way in which the process affects the development of the participants, impacting learning, teaching, and interpersonal relationships. The objective is to evaluate educational praxis in medical education. Methods: The study used questionnaires with Likert scale questions to collect responses from students, tutors, and professors. Quantitative and qualitative analysis of the responses were performed, and Fisher’s Exact test was used to verify the associations between the groups’ answers. Results: Overall, 203 responses were collected, consisting of 165 from students, 28 from tutors, and 10 from professors. The study found that both students and tutors recognize the learning gain and expertise on the subject by the tutors, which helps in understanding. The PAL program was seen by both tutors and students as contributing to academic growth. Conclusion: The PAL program was found to positively influence the performance of students and the academic life of tutors, with academic achievement and the acquisition of essential skills and competencies for professional accomplishment.